A method of lithium ion adsorption and enrichment driven by photothermal evaporation
Patent Information
- Application Number
- CN202610922882.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
[0002]盐湖卤水、海水、浓缩海水及部分工业高盐废水中含有较大规模的潜在锂资源,但该类体系通常具有锂离子浓度较低、其他共存离子(K+、Ca2+、Na+、Mg2+)等离子浓度高、盐度大和水化离子性质相近等特点,导致锂离子分离选择性、吸附动力学、长期运行稳定性和水资源消耗问题较为突出
1)、本发明以一体成型的离子筛-光热复合水凝胶作为吸附蒸发体,其能够将太阳能光热输入由单纯供热蒸发功能拓展为锂离子传质强化、局部富集、选择性捕获和淡水生成的共同驱动力,使锂离子吸附过程由光热蒸发诱导的水相通量和梯度驱动,打破了现有技术单纯依靠静态浸泡扩散或吸附后再蒸发的常规模式,有效提升了锂资源回收和淡水产出效率以及吸附蒸发体的寿命。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resource utilization technology for saline waste liquid, specifically a method for lithium-ion adsorption and enrichment driven by photothermal evaporation. Background Technology
[0002] Salt lake brines, seawater, concentrated seawater, and some high-salinity industrial wastewater contain significant potential lithium resources. However, these systems typically have low lithium-ion concentrations and other coexisting ions (K+, K+, K+, K+). + Ca 2+ Na + Mg 2+ The high plasma concentration, high salinity, and similar properties of hydrated ions lead to prominent issues in lithium-ion separation selectivity, adsorption kinetics, long-term operational stability, and water consumption.
[0003] Solar interface evaporation materials can utilize solar energy to achieve water evaporation and freshwater production. However, most evaporation materials lack the ability to selectively capture lithium ions. In high-salt environments, salt crystallization may occur at the evaporation interface, affecting continuous operation. Although existing lithium ion sieve adsorption materials can capture lithium ions through lattice vacancies or ion exchange sites, they usually only perform adsorption functions. After adsorption saturation, they need to be separated from the treatment system and regenerated separately, resulting in limited functional utilization.
[0004] Currently, lithium resource recovery technologies are mainly improved through membrane separation, electrochemical enrichment, lithium-ion sieve adsorption, and photothermal enhancement. For example, CN120136220A discloses an ion-separation solar evaporator, employing a layered structure of transmission channel—ion-separation nanofiltration membrane—capillary layer—evaporation / crystallization zone to achieve solar-driven ion separation and salt production; CN113293292B discloses a solar-driven seawater lithium extraction system that achieves lithium extraction through semiconductor photogenerated carriers and lithium-rich materials; however, the second... The essence of these technologies belongs to photochemical (electrochemical) systems, with a high degree of system complexity. For example, CN117285105B proposes a photothermal enhanced lithium-ion adsorber (core-shell nanofiber structure), and CN116966866B proposes a photothermal assisted lithium extraction nonwoven material (fiber / ion sieve composite), both focusing on photothermal enhanced adsorption. Furthermore, CN117699894A discloses a composite material evaporator (core-shell microsphere structure) capable of achieving photothermal enhanced lithium extraction and self-supplied water circulation, with a focus on evaporator structure and water circulation. Although the above technologies improve the lithium extraction process from directions such as nanofiltration membrane separation, photochemical (electrochemical) enrichment, photothermal assisted adsorption, or evaporator structure, they generally lack the coupling of selective lithium capture and solar interface evaporation for water production within the same functional material / unit. After lithium-ion adsorption saturation, it is difficult to continue freshwater production, resulting in low efficiency in lithium-ion recovery and freshwater production.
[0005] Therefore, a method is provided that enables selective capture of lithium ions and solar interface evaporation for water production within the same functional material. This method enriches lithium ions during the adsorption stage, and when the adsorption is saturated or nearly saturated, it can continue to produce fresh water and achieve water transport and salt ion regulation through the internal channels of the material. This improves the efficiency of lithium resource recovery and fresh water production, as well as the material's lifespan, and is of great significance for lithium resource recovery. Summary of the Invention
[0006] The purpose of this invention is to provide a photothermal evaporation-driven method for lithium-ion adsorption and enrichment, which enables lithium-ion adsorption and enrichment and freshwater production in the same adsorption evaporator, significantly improving the efficiency of lithium resource recovery and freshwater production, as well as the lifespan of the adsorption evaporator.
[0007] This invention is achieved through the following technical solution: A photothermal evaporation-driven method for lithium-ion adsorption and enrichment includes the following steps: S1. Provide lithium-containing brine, which contains Li. + Coexisting ions, including Na+ + K + Mg 2+ and Ca 2+ At least one of them; S2. Arrange the adsorption evaporator in the gas-liquid interface region of the lithium brine, so that the liquid supply side of the adsorption evaporator is in contact with the lithium brine, and expose the evaporation side of the adsorption evaporator to air, and apply solar irradiation or simulated solar irradiation to the evaporation side. The adsorption evaporator is a one-piece molded ion sieve-photothermal composite hydrogel, comprising a hydrophilic cross-linked hydrogel network and lithium-ion sieves and photothermal conversion materials confined within the hydrophilic cross-linked hydrogel network. The hydrophilic cross-linked hydrogel network has micron-sized water transport channels for evaporation replenishment and nano-sized or mesoporous channels for ion confinement and diffusion. The lithium-ion sieve includes components capable of reacting with Li... + Lithium-selective sites that undergo reversible ion exchange or selective insertion; photothermal conversion materials used to absorb solar radiation to form a localized photothermal field on the evaporation side; S3. Under solar irradiation or simulated solar irradiation, the photothermal conversion material converts light energy into interfacial heat energy, forming a local photothermal field on the evaporation side, thereby driving water to continuously migrate and evaporate from the liquid supply side along the micron-level water transport channels to the evaporation side. This establishes a continuous liquid replenishment flux induced by evaporation, a local ion concentration zone caused by water removal, and a temperature gradient and concentration gradient distributed along the channels inside the adsorption evaporator. S4. Driven by continuous replenishment flux, local ion concentration zones, and temperature and concentration gradients, hydrated Li in lithium-containing brine... +It enters the hydrophilic cross-linked hydrogel network and migrates to lithium-ion selective sites through nanoscale or mesoporous channels, subsequently Li + Li via lithium-ion selective sites + / H + Reversible ion exchange, lattice vacancy insertion, and surface coordination are selectively captured and stored inside the adsorption evaporator, resulting in a lithium-rich adsorption evaporator. S5, in Li + When selectively captured, coexisting ions do not enter lithium-ion selective sites due to differences in lattice vacancy size, ion hydration characteristics, charge density, or exchange energy barrier. Under the influence of evaporation-induced water flow, pore confinement, and ion hydration / charge difference, they migrate with the mother liquor backflow, diffuse, or are contained in non-lithium selective pores. S6. Collect the water vapor from the evaporation side and condense it to obtain fresh water. Simultaneously, when the lithium-rich adsorbent evaporator reaches the predetermined lithium loading, it is contacted with the desorption liquid to remove the Li-ion-selective sites trapped in the lithium ions. + The lithium-rich solution is released into the desorption solution, and then the adsorption evaporator is washed and placed again in the gas-liquid interface region of the lithium-containing brine for the next round of photothermal evaporation-driven lithium ion adsorption and enrichment. S7. Repeat steps S2 to S6 to achieve selective lithium-ion capture and solar interface evaporation for water production.
[0008] Furthermore, the lithium-containing brine of S1 is at least one of the following: salt lake brine, underground brine, geothermal brine, seawater, concentrated seawater, lithium-containing mineral leachate, decommissioned battery recycling solution, and lithium-containing industrial high-salt wastewater.
[0009] Furthermore, the adsorbent evaporator of S2 is arranged in the gas-liquid interface region of the lithium-containing brine in a floating, semi-submerged, fixed bed, fluidized bed, layered support, capillary liquid supply support or membrane support manner.
[0010] Furthermore, the hydrophilic cross-linked hydrogel network of S2 is generated by cross-linking polymerization of hydrogel building units under the action of a cross-linking agent; The hydrogel building blocks are at least one of acrylamide, acrylic acid, polyvinyl alcohol, alginate, cellulose derivatives and chitosan, wherein: alginate is at least one of sodium alginate, potassium alginate, calcium alginate and ammonium alginate; cellulose derivatives are at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose and cellulose acetate. The hydrophilic cross-linked hydrogel network has micron-sized water transport channels with a pore size of 1~1000 μm and nano-sized or mesoporous channels with a pore size of 1~100 nm.
[0011] Furthermore, the lithium-ion sieve of S2 is a hydrogen-type manganese oxide lithium-ion sieve with a spinel or spinel-like structure, which is H x Mn y O4, where 1≤x≤2, 1.2≤y≤2.2.
[0012] Furthermore, the H x Mn y O4 is H 1.33 Mn 1.67 O4 and H x Mn₂O₄, where 1 ≤ x ≤ 2.
[0013] Further, the photothermal conversion material of S2 is at least one of carbon-based photothermal materials, metal sulfides, metal oxides, MXene, conductive polymers, and metal nanomaterials, wherein: the carbon-based photothermal material includes at least one of carbon black, graphene, graphene oxide reduction products, carbon nanotubes, graphite powder, and porous carbon; the metal sulfide is at least one of molybdenum disulfide, copper sulfide, molybdenum sulfide, tungsten sulfide, and molybdenum disulfide; the metal oxide is at least one of titanium oxide, zinc oxide, copper oxide, cuprous oxide, iron(II,III) oxide, ferrous oxide, manganese oxide, cobalt oxide, and nickel oxide; and the MXene is Ti3C2T. x Ti2CT x Nb2CT x V2CT x and Mo2TiC2T x At least one of them, wherein T x The surface end groups include -O, -OH, and -F; the conductive polymer is at least one of polypyrrole, polyaniline, polydopamine, polythiophene, and polyethylenedioxythiophene; the metal nanomaterial is at least one of gold nanoparticles, silver nanoparticles, copper nanoparticles, nickel nanoparticles, and aluminum nanoparticles.
[0014] Furthermore, the adsorbent evaporator of S2 is prepared by the following method: Step 1: Preparation of lithium-ion sieves: Lithium and manganese sources are mixed at a molar ratio of (1.0~2.0):(1.2~2.2) and calcined at 500~650℃ for 2~8 h in air to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor is then reacted with a solution of 0.1~1.0 mol·L⁻¹. -1 Contacting the hydrochloric acid solution for 12–36 h, Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral, and drying at 60-100℃ for 6-24 h to obtain hydrogen-form manganese oxide lithium ion sieve. The lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium chloride; The manganese source is at least one of manganese carbonate, manganese oxide, and manganese sulfate; Step 2: Preparation of composite precursor dispersion: 0.5 g of photothermal conversion material, 1 g of hydrophilic monomer, 0.3 g of crosslinking agent and hydrogen-type manganese oxide lithium ion sieve are added to deionized water and stirred to disperse, so as to obtain a composite precursor dispersion containing lithium ion sieve and photothermal conversion material. The amount of hydrogen-type manganese oxide lithium ion sieve added is 5% to 50% of the total mass of the hydrophilic monomer and photothermal conversion material; The hydrophilic monomer is at least one of acrylamide, acrylic acid, and polyvinyl alcohol; The crosslinking agent is N,N-methylenebisacrylamide; Step 3, in-situ polymerization of hydrogel network: Add 0.02 g surfactant to the composite precursor dispersion and stir to foam, then add 0.1 g catalyst and 0.15 g initiator to allow the hydrophilic monomers to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network; The surfactant is sodium dodecyl sulfate or sodium dodecyl sulfonate; The catalyst is N,N,N,N-tetramethylethylenediamine; The initiator is ammonium persulfate; Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted monomers, surfactants, catalysts and initiators, resulting in an ion sieve-photothermal composite hydrogel, i.e., an adsorption evaporator.
[0015] Further, the S6 desorption solution is a hydrochloric acid solution, sulfuric acid solution, nitric acid solution, organic acid solution, or buffer acid solution with a concentration of 0.01~1.0 mol / L, wherein: the organic acid solution is at least one selected from glacial acetic acid solution, citric acid solution, oxalic acid solution, and tartaric acid solution; and the buffer acid solution is at least one selected from acetic acid-sodium acetate buffer, citric acid-sodium citrate buffer, citric acid-disodium hydrogen phosphate buffer, and sodium dihydrogen phosphate-disodium hydrogen phosphate buffer. Furthermore, S6 further includes: adding carbonate to the collected lithium-containing enrichment solution, so that the lithium chloride in the lithium-rich solution reacts with the carbonate to obtain lithium carbonate, wherein: the carbonate is at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.
[0016] The present invention has the following beneficial technical effects: 1) This invention uses an integrally molded ion sieve-photothermal composite hydrogel as an adsorption evaporator, which can expand the solar photothermal input from a simple heating and evaporation function to a driving force for lithium ion mass transfer enhancement, local enrichment, selective capture and freshwater generation. The lithium ion adsorption process is driven by the aqueous flux and gradient induced by photothermal evaporation, breaking the conventional mode of relying solely on static soaking diffusion or adsorption followed by evaporation in existing technologies. This effectively improves the efficiency of lithium resource recovery and freshwater production, as well as the lifespan of the adsorption evaporator.
[0017] 2) This invention utilizes a localized photothermal field and evaporation-induced replenishment to create a continuously renewing flux of lithium-containing aqueous phase and localized Li+ within the adsorption-evaporator. + Concentrated environment, making Li + Easier to reach lithium-ion sieve sites and undergo Li + / H + Exchange or vacancy insertion can achieve the coupling of lithium ion adsorption and enrichment, coexisting ion repulsion (or retention regulation) and freshwater generation in the same adsorption evaporator, thereby improving the adsorption kinetics and lithium enrichment efficiency of lithium ions.
[0018] 3) The hierarchical porous hydrogel network of the present invention can simultaneously provide capillary water supply channels, confined ion diffusion channels, and salt regulation space, enabling the inclusion of Na+... + K + Mg 2+ Ca 2+ The coexisting ions can migrate, reflux, or remain in the non-selective channels with the mother liquor, reducing their competition for lithium-ion selective sites and reducing the coverage of the evaporation interface by salt crystals. At the same time, the use of a hydrophilic cross-linked hydrogel network to limit the lithium-ion sieve and photothermal conversion material can reduce the problems of agglomeration, loss, and uneven diffusion paths caused by the use of lithium-ion sieve and photothermal conversion material alone.
[0019] 4) This invention can be applied to components including Li + Na + K + Mg 2+ Ca 2+ It enables selective adsorption and enrichment of lithium ions in high-salt systems with multiple ions coexisting, while simultaneously obtaining condensed fresh water. It is suitable for lithium resource recovery and water resource regeneration in complex systems such as salt lake brine, concentrated seawater, geothermal brine, underground brine, recycled liquid from retired batteries, and high-salt wastewater from lithium-containing industries. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the process for preparing the ion sieve-photothermal composite hydrogel in Example 1 of the present invention; Figure 2This is a schematic diagram of the adsorption-evaporation mechanism of the ion sieve-photothermal composite hydrogel prepared in this invention; Figure 3 The figure shows the lithium-ion adsorption performance test results of the ion sieve-photothermal composite hydrogel prepared in Example 1 of the present invention, wherein: (a) is the lithium-ion adsorption capacity under different pH conditions; (b) is the lithium-ion adsorption kinetic test results; and (c) is the lithium-ion adsorption isotherm fitting results. Figure 4 The graph shows the lithium-ion selectivity test results of the ion sieve-photothermal composite hydrogel prepared in Example 1 of the present invention in a multi-ion coexistence system, where: (a) is the adsorption behavior of each ion in the multi-ion system; (b) is the separation coefficient of lithium ions relative to coexisting ions. Figure 5 The figure shows the stability test results of the ion sieve-photothermal composite hydrogel adsorption and evaporation material prepared in Example 1 of the present invention during long-term solar interfacial evaporation in a simulated sea salt solution. Detailed Implementation
[0021] The present invention will be further described in detail below with reference to specific embodiments. This is an explanation of the present invention and not a limitation thereof.
[0022] A photothermal evaporation-driven method for lithium-ion adsorption and enrichment includes the following steps: S1. Provide lithium-containing brine, the lithium-containing brine containing Li + Coexisting ions, including Na+ + K + Mg 2+ and Ca 2+ At least one of them; S2. Arrange the adsorption evaporator in the gas-liquid interface region of the lithium brine, so that the liquid supply side of the adsorption evaporator is in contact with the lithium brine, and expose the evaporation side of the adsorption evaporator to air, and apply solar irradiation or simulated solar irradiation to the evaporation side. The adsorption evaporator is a one-piece molded ion sieve-photothermal composite hydrogel, comprising a hydrophilic cross-linked hydrogel network and lithium-ion sieves and photothermal conversion materials confined within the hydrophilic cross-linked hydrogel network. The hydrophilic cross-linked hydrogel network has micron-sized water transport channels for evaporation replenishment and nano-sized or mesoporous channels for ion confinement and diffusion. The lithium-ion sieve includes components capable of reacting with Li... + Lithium-selective sites that undergo reversible ion exchange or selective insertion; photothermal conversion materials used to absorb solar radiation to form a localized photothermal field on the evaporation side; S3. Under solar irradiation or simulated solar irradiation, the photothermal conversion material converts light energy into interfacial heat energy, forming a local photothermal field on the evaporation side, thereby driving water to continuously migrate and evaporate from the liquid supply side along the micron-level water transport channels to the evaporation side. This establishes a continuous liquid replenishment flux induced by evaporation, a local ion concentration zone caused by water removal, and a temperature gradient and concentration gradient distributed along the channels inside the adsorption evaporator. S4. Driven by continuous replenishment flux, local ion concentration zones, and temperature and concentration gradients, hydrated Li in lithium-containing brine... + It enters the hydrophilic cross-linked hydrogel network and migrates to lithium-ion selective sites through nanoscale or mesoporous channels, subsequently Li + Li via lithium-ion selective sites + / H + Reversible ion exchange, lattice vacancy insertion, and surface coordination are selectively captured and stored inside the adsorption evaporator, resulting in a lithium-rich adsorption evaporator. S5, in Li + When selectively captured, coexisting ions do not enter lithium-ion selective sites. Under the influence of evaporation-induced water flow, pore confinement, and ion hydration / charge differences, they migrate with the mother liquor backflow, diffuse, or are contained in non-lithium-selective pores, thereby reducing the influence of coexisting ions on Li. + Competition for adsorption sites and reduction of salt crystallization coverage on the evaporation side; S6. Collect the water vapor from the evaporation side and condense it to obtain fresh water. Simultaneously, when the lithium-rich adsorbent evaporator reaches the predetermined lithium loading, it is contacted with the desorption liquid to remove the Li-ion-selective sites trapped in the lithium ions. + The lithium-rich solution is released into the desorption solution, and then the adsorption evaporator is washed and placed again in the gas-liquid interface region of the lithium-containing brine for the next round of photothermal evaporation-driven lithium ion adsorption and enrichment. S7. Repeat steps S2 to S6 to achieve selective lithium-ion capture and solar interface evaporation for water production.
[0023] Preferably, the lithium-containing brine of S1 is at least one of salt lake brine, underground brine, geothermal brine, seawater, concentrated seawater, lithium-containing mineral leachate, decommissioned battery recycling solution, and lithium-containing high-salt industrial wastewater, and the lithium-containing brine contains Li + The concentration is 0.01~5000 mg / L, the salt mass fraction is 0.1%~30%, and the pH value is 6~14, with a preferred pH value of 10~12. Preferably, the adsorbent evaporator of S2 is arranged in the gas-liquid interface region of the lithium-containing brine in a floating, semi-submerged, fixed bed, fluidized bed, layered support, capillary liquid supply support or membrane support manner, and its liquid supply side is in continuous contact with the lithium-containing brine, while its evaporation side is in contact with air to serve as an evaporation interface.
[0024] Preferably, the intensity of solar irradiance or simulated solar irradiance in S2 is 0.5~4 sun, and more specifically, the intensity is 1~2 sun; under solar irradiance or simulated solar irradiance, the photothermal conversion material converts light energy into interfacial heat energy, forming a localized photothermal field on the evaporation side, making the temperature on the evaporation side of the adsorbent evaporator higher than the temperature of the lithium-containing brine, thus promoting the water to evaporate at a rate of 0.1 kg m -2 h -1 Up to 6.5 kg m -2 h -1 Evaporation rate.
[0025] Preferably, the hydrophilic crosslinked hydrogel network is generated by crosslinking polymerization using at least one of acrylamide, acrylic acid, polyvinyl alcohol, alginate, cellulose derivatives, and chitosan as hydrogel building units, under the action of a crosslinking agent. For example, a polyacrylamide crosslinked network is generated by reverse crosslinking polymerization of acrylamide under the action of a crosslinking agent, wherein: the alginate is at least one of sodium alginate, potassium alginate, calcium alginate, and ammonium alginate; and the cellulose derivative is at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, and cellulose acetate.
[0026] Preferably, the micron-sized water transport channels of the hydrophilic cross-linked hydrogel network have a pore size of 1~1000 μm for capillary water supply and evaporation replenishment, and the nano-sized or mesoporous channels have a pore size of 1~100 nm for the diffusion of hydrated Li+ into the lithium ion sieve in a confined environment, thereby reducing the problems of agglomeration, loss and uneven diffusion paths when the ion sieve powder is used alone.
[0027] Preferably, the lithium-ion sieve is a hydrogen-type manganese oxide lithium-ion sieve, which has a spinel or spinel-like structure and is suitable for lithium ion exchange. + Intercalated or exchanged lattice vacancies, under photothermal evaporation-induced local concentration and mass transfer activation conditions, lattice vacancies and Li + / H + Reversible exchange sites for Li + It exhibits preferential capture capability, thereby achieving selective capture of lithium ions.
[0028] Preferably, the hydrogen-type manganese oxide lithium ion sieve is H x Mn y O4 type lithium ion sieve, where 1≤x≤2, 1.2≤y≤2.2.
[0029] Preferably, the H x Mn y O4 is H 1.33 Mn 1.67 O4 and H xMn2O4, and further, the H x Mn y O4 is H 1.33 Mn 1.67 O4.
[0030] The photothermal conversion material is at least one of carbon-based photothermal materials, metal sulfides, metal oxides, MXene, conductive polymers, and metal nanomaterials, wherein: the carbon-based photothermal material includes at least one of carbon black, graphene, graphene oxide reduction products (i.e., reduced graphene oxide), carbon nanotubes, graphite powder, and porous carbon; the metal sulfide is at least one of molybdenum disulfide, copper sulfide, molybdenum sulfide, tungsten sulfide, and molybdenum disulfide; the metal oxide is at least one of titanium oxide, zinc oxide, copper oxide, cuprous oxide, iron(II,III) oxide, ferrous oxide, manganese oxide, cobalt oxide, and nickel oxide; and the MXene is Ti3C2T. x Ti2CT x Nb2CT x V2CT x and Mo2TiC2T x At least one of them, wherein T x The surface end groups include -O, -OH, and -F; the conductive polymer is at least one of polypyrrole, polyaniline, polydopamine, polythiophene, and polyethylenedioxythiophene; the metal nanomaterial is at least one of gold nanoparticles, silver nanoparticles, copper nanoparticles, nickel nanoparticles, and aluminum nanoparticles. Solar irradiation is converted into local interfacial heat energy through photothermal conversion materials, promoting water evaporation and lithium-ion mass transfer. Specifically, the local photothermal field enhances the effective mass transfer rate near lithium-ion selective sites, and evaporation-induced replenishment of the liquid allows Li... + Na continuously renews and locally accumulates around lithium-ion selective sites. + K + Mg 2+ and Ca 2+ Due to differences in lattice vacancy size, ion hydration characteristics, charge density, or exchange energy barrier, they are difficult to enter lithium-ion selective sites. Under the influence of evaporation-induced water flow, pore confinement, and differences in ion hydration / charge, they migrate with the mother liquor backflow, diffuse, or are contained in non-lithium selective pores.
[0031] Preferably, the desorption solution is a hydrochloric acid solution, sulfuric acid solution, nitric acid solution, organic acid solution or buffer acid solution with a concentration of 0.01~1.0 mol / L. More preferably, the desorption solution is a hydrochloric acid solution with a concentration of 0.01~1.0 mol / L.
[0032] Preferably, the organic acid solution is at least one selected from glacial acetic acid solution, citric acid solution, oxalic acid solution, and tartaric acid solution.
[0033] Preferably, the buffer acid solution is at least one of acetic acid-sodium acetate buffer, citrate-sodium citrate buffer, citrate-disodium hydrogen phosphate buffer, and sodium dihydrogen phosphate-disodium hydrogen phosphate buffer.
[0034] Preferably, the lithium-containing enrichment solution of S6 is mainly composed of lithium chloride. Carbonate is added to the collected lithium-containing enrichment solution, and lithium chloride reacts with carbonate to obtain lithium carbonate, wherein the carbonate is sodium carbonate or potassium carbonate.
[0035] Preferred, see Figure 1 The adsorbent evaporator is prepared by the following method: Step 1: Preparation of lithium-ion sieves: Lithium and manganese sources are mixed at a molar ratio of (1.0~2.0):(1.2~2.2) and calcined at 500~650℃ for 2~8 h in air to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor is then reacted with a solution of 0.1~1.0 mol·L⁻¹. -1 Contacting the hydrochloric acid solution for 12–36 h, Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral, and drying at 60-100℃ for 6-24 h to obtain hydrogen-form manganese oxide lithium ion sieve. The lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium chloride; The manganese source is at least one of manganese carbonate, manganese oxide, and manganese sulfate; Step 2: Preparation of composite precursor dispersion: 0.5 g of photothermal conversion material, 1 g of hydrophilic monomer, 0.3 g of crosslinking agent and hydrogen-type manganese oxide lithium ion sieve are added to deionized water and stirred to disperse, so as to obtain a composite precursor dispersion containing lithium ion sieve and photothermal conversion material. The amount of hydrogen-type manganese oxide lithium ion sieve added is 5% to 50% of the total mass of the hydrophilic monomer and photothermal conversion material; The hydrophilic monomer is at least one of acrylamide, acrylic acid, and polyvinyl alcohol, preferably acrylamide; The crosslinking agent is N,N-methylenebisacrylamide; Step 3, in-situ polymerization of hydrogel network: Add 0.02 g surfactant to the composite precursor dispersion and stir to foam, then add 0.1 g catalyst and 0.15 g initiator to allow the hydrophilic monomers to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network; The surfactant is sodium dodecyl sulfate or sodium dodecyl sulfonate; The catalyst is N,N,N,N-tetramethylethylenediamine; The initiator is ammonium persulfate; Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted monomers, surfactants, catalysts and initiators, resulting in an ion sieve-photothermal composite hydrogel, i.e., an adsorption evaporator.
[0036] Preferably, in step 1, the molar ratio of lithium source to manganese source is 1.33:1.67.
[0037] Preferably, in step 2, the amount of hydrogen-form manganese oxide lithium ion sieve added is 10% to 30% of the total mass of the hydrophilic monomer and the photothermal conversion material. More specifically, the amount of hydrogen-form manganese oxide lithium ion sieve added is 15% to 25% of the total mass of the hydrophilic monomer and the photothermal conversion material.
[0038] Example 1 Step 1: Preparation of lithium-ion sieves: Lithium carbonate and manganese carbonate were mixed according to a molar ratio of lithium to manganese of 1.33:1.67 and calcined at 550℃ for 4 h in air atmosphere to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.5 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 24 h, and then perform Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral and drying at 60°C for 24 h to obtain a hydrogen-form manganese oxide lithium ion sieve with the chemical formula H. 1.33 Mn 1.67 O4; Step 2: Preparation of the composite precursor dispersion: Take 0.5 g molybdenum disulfide, 1 g acrylamide, and 0.3 g N,N-methylenebisacrylamide, and add H according to 20% of the total mass of acrylamide and molybdenum disulfide. 1.33 Mn 1.67 O4, then molybdenum disulfide, acrylamide, N,N-methylenebisacrylamide and H 1.33 Mn 1.67 O4 was added to deionized water and stirred to disperse, resulting in a composite precursor dispersion containing lithium ion sieves and photothermal conversion materials. Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow acrylamide to undergo free radical polymerization and crosslinking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted acrylamide, sodium dodecyl sulfate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain the ion sieve-photothermal composite hydrogel, i.e., the adsorbent evaporator, denoted as MHA-20.
[0039] Example 2 Step 1: Preparation of lithium-ion sieves: Lithium hydroxide and manganese oxide were mixed according to a molar ratio of lithium to manganese of 1:1.2 and calcined at 500℃ for 8 h in air atmosphere to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.1 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 12 h, and then perform Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral and drying at 80°C for 15 h to obtain a hydrogen-form manganese oxide lithium ion sieve with the chemical formula HMn. 1.2 O4; Step 2: Preparation of the composite precursor dispersion: Take 0.5 g carbon black, 1 g acrylic acid, and 0.3 g N,N-methylenebisacrylamide, and add HMn according to 10% of the total mass of acrylic acid and carbon black. 1.2 O4, then carbon black, acrylic acid, N,N-methylenebisacrylamide and HMn 1.2 O4 was added to deionized water and stirred to disperse, resulting in a composite precursor dispersion containing lithium ion sieves and photothermal conversion materials. Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfonate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow acrylic acid to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted acrylic acid, sodium dodecyl sulfonate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0040] Example 3 Step 1: Preparation of lithium-ion sieves: Lithium carbonate and manganese sulfate were mixed according to a molar ratio of lithium to manganese of 2:2.2 and calcined at 600℃ for 6 h in air atmosphere to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 1 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 18 h, and then perform Li + / H +Ion exchange was used to remove lattice lithium ions, followed by washing until neutral and drying at 100°C for 6 h to obtain a hydrogen-form manganese oxide lithium ion sieve with the chemical formula H₂Mn. 2.2 O4; Step 2: Preparation of the composite precursor dispersion: Take 0.5 g of ferric oxide, 1 g of acrylic acid, and 0.3 g of N,N-methylenebisacrylamide, and add H2Mn according to 5% of the total mass of acrylic acid and ferric oxide. 2.2 O4, then iron oxide, acrylic acid, N,N-methylenebisacrylamide and H2Mn 2.2 O4 was added to deionized water and stirred to disperse, resulting in a composite precursor dispersion containing lithium ion sieves and photothermal conversion materials. Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow acrylic acid to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted acrylic acid, sodium dodecyl sulfate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0041] Example 4 Step 1: Preparation of lithium-ion sieves: Lithium chloride and manganese sulfate were mixed according to a lithium to manganese molar ratio of 1:2 and calcined at 650℃ for 2 h in air to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.3 mol·L⁻¹ solution of lithium chloride and manganese sulfate. -1 Contact with hydrochloric acid solution for 24 h, and then perform Li + / H + Ion exchange was used to remove lattice lithium ions, and the mixture was washed until neutral and dried at 70°C for 10 h to obtain a hydrogen-type manganese oxide lithium ion sieve with the chemical formula HMn2O4. Step 2, Preparation of composite precursor dispersion: Take 0.5 g Ti2CT x 1 g acrylamide, 0.3 g N,N-methylenebisacrylamide, and according to acrylamide and Ti2CT x Take 15% of the total mass of HMn2O4, then take Ti2CT. x Acrylamide, N,N-methylenebisacrylamide and HMn2O4 were added to deionized water and stirred to disperse, thus obtaining a composite precursor dispersion containing lithium ion sieve and photothermal conversion material; Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow acrylic acid to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted acrylamide, sodium dodecyl sulfate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0042] Example 5 Step 1: Preparation of lithium-ion sieves: Lithium chloride and manganese sulfate were mixed according to a molar ratio of lithium to manganese of 2:1.2 and calcined at 575°C for 5 h in air to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.2 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 36 h, and perform Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral and drying at 90°C for 20 h to obtain a hydrogen-form manganese oxide lithium ion sieve with the chemical formula H₂Mn. 1.2 O4; Step 2: Preparation of the composite precursor dispersion: Take 0.5 g polydopamine, 1 g acrylamide, and 0.3 g N,N-methylenebisacrylamide, and add H2Mn according to 50% of the total mass of acrylamide and polydopamine. 1.2 O4, then polydopamine, acrylamide, N,N-methylenebisacrylamide and H2Mn 1.2 O4 was added to deionized water and stirred to disperse, resulting in a composite precursor dispersion containing lithium ion sieves and photothermal conversion materials. Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow acrylic acid to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted acrylamide, sodium dodecyl sulfate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0043] Example 6 Step 1: Preparation of lithium-ion sieves: Lithium chloride and manganese oxide were mixed according to a lithium to manganese molar ratio of 1:2.2 and calcined at 500℃ for 7 h in air atmosphere to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.8 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 30 h, and carry out Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral and drying at 100°C for 18 h to obtain a hydrogen-form manganese oxide lithium ion sieve with the chemical formula HMn. 2.2 O4; Step 2: Preparation of the composite precursor dispersion: Take 0.5 g of copper nanoparticles, 1 g of polyvinyl alcohol, and 0.3 g of N,N-methylenebisacrylamide, and add HMn according to 25% of the total mass of polyvinyl alcohol and copper nanoparticles. 2.2 O4, then copper nanoparticles, polyvinyl alcohol, N,N-methylenebisacrylamide and HMn 2.2 O4 was added to deionized water and stirred to disperse, resulting in a composite precursor dispersion containing lithium ion sieves and photothermal conversion materials. Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow polyvinyl alcohol to undergo free radical polymerization and crosslinking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted polyvinyl alcohol, sodium dodecyl sulfate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0044] Example 7 Step 1: Preparation of lithium-ion sieves: Lithium hydroxide and manganese carbonate were mixed according to a lithium to manganese molar ratio of 2:2 and calcined at 650℃ for 3 h in air atmosphere to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor was then reacted with a 0.6 mol·L⁻¹ solution. -1 Contact with hydrochloric acid solution for 20 h, and then perform Li + / H + Ion exchange was used to remove lattice lithium ions, and the mixture was washed until neutral and dried at 60°C for 8 h to obtain a hydrogen-type manganese oxide lithium ion sieve with the chemical formula H2Mn2O4. Step 2: Preparation of composite precursor dispersion: Take 0.5 g zinc oxide, 1 g polyvinyl alcohol, and 0.3 g N,N-methylenebisacrylamide, and add H2Mn2O4 according to 30% of the total mass of polyvinyl alcohol and zinc oxide. Then add zinc oxide, polyvinyl alcohol, N,N-methylenebisacrylamide and H2Mn2O4 to deionized water, stir and disperse to obtain a composite precursor dispersion containing lithium ion sieve and photothermal conversion material; Step 3, In-situ polymerization of hydrogel network: Add 0.02 g sodium dodecyl sulfonate to the composite precursor dispersion and stir to foam. Then add 0.1 g N,N,N,N-tetramethylethylenediamine and 0.15 g ammonium persulfate to allow polyvinyl alcohol to undergo free radical polymerization and crosslinking reaction to form a three-dimensional porous hydrogel network. Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted polyvinyl alcohol, sodium dodecyl sulfonate, N,N,N,N-tetramethylethylenediamine and ammonium persulfate residues, to obtain ion sieve-photothermal composite hydrogel, i.e., adsorption evaporator.
[0045] The adsorbent evaporator prepared in Example 1 was placed in the gas-liquid interface region of a lithium-containing brine solution, with the liquid supply side of the adsorbent evaporator in contact with the lithium-containing brine solution, and the evaporation side of the adsorbent evaporator exposed to air. Solar irradiation or simulated solar irradiation was applied to the evaporation side, causing molybdenum disulfide to absorb light energy and generate a localized thermal field on the evaporation side. Figure 2 As shown, under illumination, water is continuously supplied from the liquid supply side along the micron-sized channels of the hydrogel and vaporizes on the evaporation side. As water is continuously removed, a continuous aqueous flux is formed inside the adsorbent evaporator, pointing from the liquid supply side to the light-receiving evaporation side. Simultaneously, local ion concentration zones, temperature gradients, and concentration gradients are formed. (Li) + Entering the hydrogel network along with the aqueous phase and flowing into the hydrogen-type manganese oxide lithium ion sieve (H 1.33 Mn 1.67 Li (O4) + / H + Exchange sites or lithium vacancy migrations are selectively captured; in this process, Na... + K + Mg 2+ and Ca 2+ Due to differences in hydration characteristics, charge density, and lattice vacancy compatibility, coexisting ions, including those in the lithium-ion sieve, have difficulty entering lithium-ion selective sites. They migrate with the mother liquor recirculation, diffuse, or remain in non-lithium-selective channels. Therefore, the photothermal evaporation process of the adsorbent evaporator prepared in this invention not only achieves photothermal evaporation for water production but also serves as a driving force for Li... + Mass transfer dynamics of migration, renewal, and local enrichment enable light-driven lithium-ion adsorption and enrichment.
[0046] To verify the performance of the adsorbent evaporator prepared in this invention, its lithium-ion adsorption and enrichment performance, lithium selectivity, and salt resistance were tested, and the results are as follows: 1) Lithium-ion adsorption and enrichment performance: Weigh 20 g of the ion sieve-photothermal composite hydrogel prepared in Example 1, and add it to a container with an initial lithium-ion concentration of 100 mg·L⁻¹. -1 In a simulated brine solution, the solution was placed in a constant-temperature shaker at 25°C and shaken at 300 rpm for 12 h until adsorption equilibrium was reached. The pH of the solution was adjusted to 6–12 to investigate the changes in the adsorption capacity of the hydrogel for lithium ions under different pH conditions. After adsorption equilibrium was reached, the solution was filtered through a microporous membrane with a pore size of 0.22 μm, and the filtrate was collected. The residual lithium ion concentration in the solution was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the lithium ion adsorption efficiency was calculated using the following formula. R e (%) equilibrium adsorption capacity Q e (mg·g -1 ): In the formula, C 0 represents the initial lithium-ion concentration, in mg·L⁻¹. -1 ; C e To balance the lithium ion concentration, the unit is mg·L. -1 ; V The volume is the solution volume, in liters (L). m The mass of the composite hydrogel is expressed in grams. from Figure 3 (a) It can be seen that as the pH of the simulated brine increases, the adsorption capacity of MHA-20 for lithium ions gradually increases. Under the condition of pH=12, the lowest lithium ion adsorption capacity can reach 29.85 mg·g -1 Because under alkaline conditions, H+ in the solution... + A decrease in concentration is beneficial to H 1.33 Mn 1.67 Li in O4 lithium ion sieve + / H + The exchange equilibrium shifts towards lithium-ion adsorption, thereby improving the material's ability to capture lithium ions; To further evaluate the adsorption process, MHA-20 was subjected to adsorption isotherms in lithium-ion solutions with different initial concentrations, and adsorption kinetics were tested at different contact times. Figure 3 (b) and Figure 3(c) It can be seen that the adsorption process of lithium ions by MHA-20 can be well matched with the pseudo-second-order kinetic model, indicating that ion exchange and chemisorption play the main roles in the lithium ion capture process, and that MHA-20 has a high lithium ion adsorption capacity, which can meet the requirements of lithium ion enrichment in lithium-containing brine.
[0047] 2) Lithium selectivity test in multi-ion coexistence systems: using Li-containing... + (40 mg L) -1 Na + (241 mg L) -1 ), K + (443 mg L) -1 ), Mg 2+ (501 mg L) -1 ) and Ca 2+ (535 mg L) -1 Using simulated brine as the test solution, 20 mg of the composite hydrogel prepared in Example 1 was weighed and added to 20 mL of simulated brine solution. The solution was shaken at 300 rpm for 24 h at 298 K. After adsorption equilibrium was reached, the equilibrium concentration of each ion in the solution was determined by ICP-OES, and the separation coefficient of lithium ions relative to coexisting ions was measured. Calculate according to formulas (3) and (4): In the formula: Me represents the coexisting ion, and Na represents the Na+ ion. + K + Mg 2+ or Ca 2+ , This represents the lithium-ion partition coefficient. The partition coefficient of the coexisting ions; C 0 represents the initial lithium-ion concentration, in mg·L⁻¹. -1 ; C e To balance the lithium ion concentration, the unit is mg·L. -1 ; V The volume is the solution volume, in liters (L). m The mass of the composite hydrogel is expressed in grams. from Figure 4 It can be seen that: in Na + K + Mg 2+ and Ca 2+ Under conditions where coexisting ions are present, MHA-20 has a positive effect on Li + It exhibits significant preferential adsorption capacity for Li + Relative to K+ Ca 2+ Na + and Mg 2+ All have high separation coefficients, among which: Li + / Mg 2+ Li + / Ca 2+ Li + / Na + Li + / K + The separation coefficients reached 60, 100, 50, and 90, respectively; these results indicate that even in high-salt systems where highly competitive divalent cations such as magnesium ions are present, the H+ ions immobilized in the hydrogel network can achieve separation. 1.33 Mn 1.67 The fact that the O4 lithium ion sieve can still maintain effective lithium ion sieving and selective ion exchange capabilities indicates that the MHA-20 prepared by this invention is suitable for the selective enrichment of lithium ions in salt lake brine, seawater, concentrated seawater, geothermal brine and lithium-containing high-salt wastewater.
[0048] 3) Solar interface evaporation and high-salt stability test: The composite hydrogel, saturated with lithium ion adsorption, was cut into regular blocks. A high-concentration salt solution was used as a simulated sea salt solution, with the lower surface of the blocks in contact with the solution and the upper surface exposed to air. The evaporation experiment was conducted at an ambient temperature of 20℃ and a relative humidity of 40%, with simulated sunlight (AM 1.5G, light intensity 1 kW·m²). -2 The system mass change is recorded in real time by an electronic balance, and the evaporation rate J (kg·m³) is calculated according to formula (5). -2 ·h -1 ): In the formula: Δ m (kg) represents the water mass loss per unit time. A (m) 2 ) represents the evaporation interface area, Δ t Evaporation time, in hours; Specifically, to evaluate the continuous operational stability of the composite hydrogel MHA-20 in a high-salt environment, the adsorption-saturated composite hydrogel was placed in a 20 wt.% simulated sea salt solution and subjected to a long-term solar interface evaporation test under 1 sun illumination, with a total operating time exceeding 150 h. During the test, the evaporation rate was recorded periodically over time, and the salt distribution at the evaporation interface and within the material was analyzed using optical observation and scanning electron microscopy. (See [link to relevant documentation]). Figure 5 It can be seen that MHA-20 can maintain stable interfacial evaporation performance in high-salt systems, with an evaporation rate of 2.11 kg·m³. -2·h -1 After 150 hours of continuous operation, no obvious salt crystallization was observed on the surface of the material, indicating that MHA-20 can continue to be used as a solar interface evaporation material after adsorbing lithium ions. Through the continuous water supply of the hydrophilic porous network and the internal salt regulation, it can achieve stable water production and salt-resistant operation under high salt conditions.
[0049] In summary, this invention, through interfacial evaporation generated by solar photothermal conversion, not only provides the energy required for water evaporation but also simultaneously drives the continuous replenishment of lithium-containing brine within the adsorption evaporation body. + This method enhances migration, local concentration, and selective capture, coupling water transport, local ion concentration, lithium-ion migration activation, selective adsorption enrichment, and freshwater generation within the same adsorbent-evaporator. This allows the lithium-ion adsorption and enrichment process to be driven by photothermal energy, unlike conventional methods that rely solely on static immersion diffusion or adsorption followed by evaporation. It effectively improves lithium resource recovery and freshwater production efficiency, as well as the lifetime of the adsorbent-evaporator. Experimental results show that for a pH of 12 and an initial Li... + A lithium-containing brine solution with a concentration of 100 mg / L, at 25°C, exhibits the adsorption-evaporation properties of the present invention for Li... + The adsorption capacity reached over 20 mg / g, with a maximum of over 29 mg / g; in the presence of Li + Na + K + Mg 2+ and Ca 2+ In multi-ion coexistence systems, Li + Relative to Mg 2+ The separation coefficient reached over 50; under 1 sun solar irradiation, for a 20 wt.% simulated sea salt solution, the evaporation rate of the adsorbent evaporator reached 2.0 kgm³. -2 h -1 The above parameters are required, and the equipment can operate continuously for more than 150 hours without significant salt crystallization on the evaporation side.
Claims
1. A method for lithium-ion adsorption and enrichment driven by photothermal evaporation, characterized in that, Includes the following steps: S1. Provide lithium-containing brine, which contains Li. + Coexisting ions, including Na+ + K + Mg 2+ and Ca 2+ At least one of them; S2. Arrange the adsorption evaporator in the gas-liquid interface region of the lithium brine, so that the liquid supply side of the adsorption evaporator is in contact with the lithium brine, and expose the evaporation side of the adsorption evaporator to air, and apply solar irradiation or simulated solar irradiation to the evaporation side. The adsorption evaporator is a one-piece molded ion sieve-photothermal composite hydrogel, comprising a hydrophilic cross-linked hydrogel network and lithium-ion sieves and photothermal conversion materials confined within the hydrophilic cross-linked hydrogel network. The hydrophilic cross-linked hydrogel network has micron-sized water transport channels for evaporation replenishment and nano-sized or mesoporous channels for ion confinement and diffusion. The lithium-ion sieve includes components capable of reacting with Li... + Lithium-selective sites that undergo reversible ion exchange or selective insertion; photothermal conversion materials used to absorb solar radiation to form a localized photothermal field on the evaporation side; S3. Under solar irradiation or simulated solar irradiation, the photothermal conversion material converts light energy into interfacial heat energy, forming a local photothermal field on the evaporation side, thereby driving water to continuously migrate and evaporate from the liquid supply side along the micron-level water transport channels to the evaporation side. This establishes a continuous liquid replenishment flux induced by evaporation, a local ion concentration zone caused by water removal, and a temperature gradient and concentration gradient distributed along the channels inside the adsorption evaporator. S4. Driven by continuous replenishment flux, local ion concentration zones, and temperature and concentration gradients, hydrated Li in lithium-containing brine... + It enters the hydrophilic cross-linked hydrogel network and migrates to lithium-ion selective sites through nanoscale or mesoporous channels, subsequently Li + Li via lithium-ion selective sites + / H + Reversible ion exchange, lattice vacancy insertion, and surface coordination are selectively captured and stored inside the adsorption evaporator, resulting in a lithium-rich adsorption evaporator. S5, in Li + When selectively captured, coexisting ions do not enter lithium-ion selective sites due to differences in lattice vacancy size, ion hydration characteristics, charge density, or exchange energy barrier. Under the influence of evaporation-induced water flow, pore confinement, and ion hydration / charge difference, they migrate with the mother liquor backflow, diffuse, or are contained in non-lithium selective pores. S6. Collect the water vapor from the evaporation side and condense it to obtain fresh water. Simultaneously, when the lithium-rich adsorbent evaporator reaches the predetermined lithium loading, it is contacted with the desorption liquid to remove the Li-ion-selective sites trapped in the lithium ions. + The lithium-rich solution is released into the desorption solution, and then the adsorption evaporator is washed and placed again in the gas-liquid interface region of the lithium-containing brine for the next round of photothermal evaporation-driven lithium ion adsorption and enrichment. S7. Repeat steps S2 to S6 to achieve selective lithium-ion capture and solar interface evaporation for water production.
2. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The lithium-containing brine of S1 is at least one of the following: salt lake brine, underground brine, geothermal brine, seawater, concentrated seawater, lithium-containing mineral leachate, decommissioned battery recycling solution, and lithium-containing industrial high-salt wastewater.
3. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The adsorption evaporator of S2 is arranged in the gas-liquid interface region of lithium brine in the form of floating, semi-submerged, fixed bed, fluidized bed, layered support, capillary liquid supply support or membrane support.
4. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The hydrophilic cross-linked hydrogel network of S2 is generated by cross-linking polymerization of hydrogel building units under the action of a cross-linking agent; The hydrogel building blocks are at least one of acrylamide, acrylic acid, polyvinyl alcohol, alginate, cellulose derivatives and chitosan, wherein: alginate is at least one of sodium alginate, potassium alginate, calcium alginate and ammonium alginate; cellulose derivatives are at least one of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose and cellulose acetate. The hydrophilic cross-linked hydrogel network has micron-sized water transport channels with a pore size of 1~1000 μm and nano-sized or mesoporous channels with a pore size of 1~100 nm.
5. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The lithium-ion sieve of S2 is a hydrogen-type manganese oxide lithium-ion sieve with a spinel or spinel-like structure, which is H x Mn y O4, where 1≤x≤2, 1.2≤y≤2.
2.
6. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 5, characterized in that, The H x Mn y O4 is H 1.33 Mn 1.67 O4 and H x Mn₂O₄, where 1 ≤ x ≤ 2.
7. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The photothermal conversion material of S2 is at least one of carbon-based photothermal materials, metal sulfides, metal oxides, MXene, conductive polymers, and metal nanomaterials, wherein: the carbon-based photothermal material includes at least one of carbon black, graphene, graphene oxide reduction products, carbon nanotubes, graphite powder, and porous carbon; the metal sulfide is at least one of molybdenum disulfide, copper sulfide, molybdenum sulfide, tungsten sulfide, and molybdenum disulfide; the metal oxide is at least one of titanium oxide, zinc oxide, copper oxide, cuprous oxide, iron(II,III) oxide, ferrous oxide, manganese oxide, cobalt oxide, and nickel oxide; and the MXene is Ti3C2T. x Ti2CT x Nb2CT x V2CT x and Mo2TiC2T x At least one of them, wherein T x The surface end groups include -O, -OH, and -F; the conductive polymer is at least one of polypyrrole, polyaniline, polydopamine, polythiophene, and polyethylenedioxythiophene; the metal nanomaterial is at least one of gold nanoparticles, silver nanoparticles, copper nanoparticles, nickel nanoparticles, and aluminum nanoparticles.
8. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 7, characterized in that, The adsorbent evaporator of S2 is prepared by the following method: Step 1: Preparation of lithium-ion sieves: Lithium and manganese sources are mixed at a molar ratio of (1.0~2.0):(1.2~2.2) and calcined at 500~650℃ for 2~8 h in air to obtain a lithium manganese oxide precursor. The lithium manganese oxide precursor is then reacted with a solution of 0.1~1.0 mol·L⁻¹. -1 Contacting the hydrochloric acid solution for 12–36 h, Li + / H + Ion exchange was used to remove lattice lithium ions, followed by washing until neutral, and drying at 60-100℃ for 6-24 h to obtain hydrogen-form manganese oxide lithium ion sieve. The lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium chloride; The manganese source is at least one of manganese carbonate, manganese oxide, and manganese sulfate; Step 2: Preparation of composite precursor dispersion: 0.5 g of photothermal conversion material, 1 g of hydrophilic monomer, 0.3 g of crosslinking agent and hydrogen-type manganese oxide lithium ion sieve are added to deionized water and stirred to disperse, so as to obtain a composite precursor dispersion containing lithium ion sieve and photothermal conversion material. The amount of hydrogen-type manganese oxide lithium ion sieve added is 5% to 50% of the total mass of the hydrophilic monomer and photothermal conversion material; The hydrophilic monomer is at least one of acrylamide, acrylic acid, and polyvinyl alcohol; The crosslinking agent is N,N-methylenebisacrylamide; Step 3, in-situ polymerization of hydrogel network: Add 0.02 g surfactant to the composite precursor dispersion and stir to foam, then add 0.1 g catalyst and 0.15 g initiator to allow the hydrophilic monomers to undergo free radical polymerization and cross-linking reaction to form a three-dimensional porous hydrogel network; The surfactant is sodium dodecyl sulfate or sodium dodecyl sulfonate; The catalyst is N,N,N,N-tetramethylethylenediamine; The initiator is ammonium persulfate; Step 4, Post-processing: The three-dimensional porous hydrogel network is immersed in deionized water to remove unreacted monomers, surfactants, catalysts and initiators, resulting in an ion sieve-photothermal composite hydrogel, i.e., an adsorption evaporator.
9. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, The S6 desorption solution is a hydrochloric acid solution, sulfuric acid solution, nitric acid solution, organic acid solution, or buffer acid solution with a concentration of 0.01~1.0 mol / L, wherein: the organic acid solution is one or more of glacial acetic acid solution, citric acid solution, oxalic acid solution, and tartaric acid solution; and the buffer acid solution is at least one of acetic acid-sodium acetate buffer, citric acid-sodium citrate buffer, citric acid-disodium hydrogen phosphate buffer, and sodium dihydrogen phosphate-disodium hydrogen phosphate buffer.
10. The method for lithium-ion adsorption and enrichment driven by photothermal evaporation according to claim 1, characterized in that, S6 further includes: adding carbonate to the collected lithium-containing enrichment solution, so that the lithium chloride in the lithium-rich solution reacts with the carbonate to obtain lithium carbonate, wherein: the carbonate is at least one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.
Citation Information
Patent Citations
A solar-powered seawater lithium extraction system and its preparation method
CN113293292B
A nonwoven material with photothermal-assisted lithium extraction function, its preparation method and application
CN116966866B
Photothermal enhanced lithium ion adsorber for seawater lithium extraction, device and application
CN117285105B
Ion separation solar evaporator and preparation method thereof
CN120136220A